2024
DOI: 10.1186/s12951-024-02298-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-based delivery strategies for tumor therapy: an update on modification, loading, and clinical application

Qian Yang,
Shisheng Li,
Haibo Ou
et al.

Abstract: Malignancy is a major public health problem and among the leading lethal diseases worldwide. Although the current tumor treatment methods have therapeutic effect to a certain extent, they still have some shortcomings such as poor water solubility, short half-life, local and systemic toxicity. Therefore, how to deliver therapeutic agent so as to realize safe and effective anti-tumor therapy become a problem urgently to be solved in this field. As a medium of information exchange and material transport between c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 224 publications
0
4
0
Order By: Relevance
“…First, exosomes were collected using differential ultracentrifugation, which is a complicated method which cannot remove the debris inevitably produced during the collection process. Thus, for applications in clinical settings, easier methods of collecting high-quality exosomes are warranted, such as size exclusion chromatography, dense gradient centrifugation, and immunoaffinity capture [14]. Second, although the omentum was used as the exosome source, a laparotomy must be performed to utilize the omentum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, exosomes were collected using differential ultracentrifugation, which is a complicated method which cannot remove the debris inevitably produced during the collection process. Thus, for applications in clinical settings, easier methods of collecting high-quality exosomes are warranted, such as size exclusion chromatography, dense gradient centrifugation, and immunoaffinity capture [14]. Second, although the omentum was used as the exosome source, a laparotomy must be performed to utilize the omentum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if patient-derived exosomes can be used as transport carriers, immune reactions during administration may be avoided. Various preclinical studies have revealed the potential of exosomes as carriers for nucleic acid compounds (such as siRNA and shRNA), proteins (such as 20S proteasome and catalase), and drugs (such as dopamine, paclitaxel, and doxorubicin) [11,14,15]. Furthermore, we recently demonstrated the efficacy of exosomes as microRNA carriers [16,17].…”
Section: Introductionmentioning
confidence: 89%
“…It is possible to engineer tissue-type-specific or cell-type-specific targeting ligands onto their surface [83], and exosomes can be loaded with various cargos, including nucleic acids, proteins, and low-molecular-weight therapeutic agents [12]. Furthermore, the potential for personalized medication is offered through the readministration of isolated exosomes loaded with therapeutic agents into the patient [84,85]. However, numerous challenges must be addressed to render exosomes applicable for therapeutic purposes in the treatment of central nervous system diseases.…”
Section: Noninvasive Delivery Of Exosomes To the Brainmentioning
confidence: 99%
“…Additionally, a better understanding of the molecules dictating the docking and uptake of EVs can help improve the effectiveness of emerging exosome-based delivery strategies and technologies for cancer therapy developed by biotech companies, either as platforms to load and deliver therapeutic miRNAs and/or proteins or as immunomodulating agents [ 157 , 158 , 159 , 160 , 161 , 162 , 163 ].…”
Section: Concluding Remarks: Impact Of Tev-docking/uptake Molecular D...mentioning
confidence: 99%